1976
DOI: 10.1021/bi00650a026
|View full text |Cite
|
Sign up to set email alerts
|

Structure of the concanavalin A-methyl α-D-mannopyranoside complex at 6-Å resolution

Abstract: The carbohydrate binding site of concanavalin A has been identified in crystals of the concanavalin A-methyl alpha-D-mannopyranoside complex and is 35 A from the iodophenol binding site (K. D. Hardman and C. F. Ainsworth (1973), Biochemistry 12,4442), which has been postulated to be adjacent to the carbohydrate-specific binding site (Edelman et al. (1972), Proc. Natl. Acad. Sci. U.S.A. 69, 2580). The crystals are orthorhombic in space group C222(1) and crystal denisty measurements indicate a protein mass of fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
38
0

Year Published

1979
1979
1994
1994

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(43 citation statements)
references
References 28 publications
5
38
0
Order By: Relevance
“…These studies suggested that peptides might be found that competitively inhibit other classes of carbohydrate-binding proteins An amino-terminal library of random octapeptides consisting of =1.4 x 109 members (-5% of all possible octamers) was affinity-purified against immobilized Con A. When phage were eluted by a low-pH citrate buffer to dissociate the phage-Con A complex, the sequence Tyr-Xaa-Tyr (where Xaa is predominantly a hydrophilic amino acid) was Although a number of hydrophobic binding sites exist on the Con A surface, including sites for fluorescent dansyl derivatives (35,36), tryptophan or indoleacetic acid (37), and benzoic acid derivatives (38), a number of studies indicate that the chromogenic ligand p-nitrophenyl a-D-mannopyranoside binds at the saccharide binding site (18,39,40 (1, 42). The sugar interacts with the lectin through a network of seven hydrogen bonds that connect four oxygens of the ligand with five amino acid residues of the protein.…”
Section: Resultsmentioning
confidence: 99%
“…These studies suggested that peptides might be found that competitively inhibit other classes of carbohydrate-binding proteins An amino-terminal library of random octapeptides consisting of =1.4 x 109 members (-5% of all possible octamers) was affinity-purified against immobilized Con A. When phage were eluted by a low-pH citrate buffer to dissociate the phage-Con A complex, the sequence Tyr-Xaa-Tyr (where Xaa is predominantly a hydrophilic amino acid) was Although a number of hydrophobic binding sites exist on the Con A surface, including sites for fluorescent dansyl derivatives (35,36), tryptophan or indoleacetic acid (37), and benzoic acid derivatives (38), a number of studies indicate that the chromogenic ligand p-nitrophenyl a-D-mannopyranoside binds at the saccharide binding site (18,39,40 (1, 42). The sugar interacts with the lectin through a network of seven hydrogen bonds that connect four oxygens of the ligand with five amino acid residues of the protein.…”
Section: Resultsmentioning
confidence: 99%
“…The MS11 synthetic peptide analogues used in this study (Table 1) correspond to regions both of conserved sequence (residues [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35], 41-50, 48-60, and 69-84) and of variable sequence (residues 107-121, 121-134, and 135-151) between pilin from various gonococcal strains (12). Fourteen rabbits were immunized with the seven peptides conjugated to thyroglobulin (two rabbits per conjugate).…”
Section: Resultsmentioning
confidence: 99%
“…A high percentage of the residues that hydrogen-bond the ligand in the binding sites of the few carbohydrate-binding proteins whose three-dimensional structures have been determined (4,(24)(25)(26)(27) are present in turns. We felt that an antibody generated against a predicted turn in the conserved region of gonococcal pilin might block pili from binding eukaryotic membranes.…”
Section: Discussionmentioning
confidence: 99%
“…Initial expectations that a structure of the complex of concanavalin A and a saccharide would soon follow were not realized. Co-crystallization of concanavalin A and mannoside was reported by Hardman & Ainsworth (1976) but the crystals suffered from lattice disorders, which limited the resolution to 6 A. The saccharide-binding site was located, however.…”
mentioning
confidence: 99%